Diet, microhabitat and bioacoustics of Ansonia latidisca (amphibia: anura: bufonidae), the bornean rainbow toad at Gunung Penrissen, Sarawak, Malaysia - Ong, Jia Jet (Universiti Malaysia Sarawak (UNIMAS), 2014)
This thesis presents data on the natural history of A. latidisca, a little known bufonid amphibian species, through an investigation of the diet, microhabitat use and bioacoustics of a population at Gunung Penrissen, Sarawak, Malaysia (north-western Borneo). Standard sampling techniques, including visual encounter surveys and spot sampling methods at potential habitats, were adopted. Dietary data obtained by stomach flushing 46 adults show 12 food categories, dominated by formicids (ants). These results categorize A. latidisca as a dietary specialist, with an active preference for feeding on small prey that show clumped distribution. A. latidisca is the only known arboreal species of its genus, as identified by this study, and is typically associated with tree trunks, while known congeners are associated with low saplings during the non-breeding season. Patterns of microhabitat utilization shown by the sexes of A. latidisca are suggestive of substantial resource sharing. The advertisement calls of male A. latidisca consist of two segments. The first segment is usually short (3–5 notes of 5–12 pulses each), and immediately followed by a longer, repeated and uninterrupted note of 112–155 pulses up to 10 seconds. Mean dominant frequencies are around 5.5 kHz, and the fundamental frequency is around 2.7 kHz. This study has added important baseline knowledge to a poorly known Bornean endemic. The brightly coloured skin, while providing camouflage (specifically, mimicry of mosses and other epiphytic vegetation), may also have aposematic function (specifically, including isolated red pigments on the dorsum of body and limbs). Additional specializations in its vi morphology noted include dilated finger tips and relatively elongated body and limbs, features not observed in congeneric species, and considered here as adaptive for an arboreal lifestyle.